(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
Technological advances have created a series of major problems associated with environmental pollution especially during the timings of industrial revolution in the eighteenth and nineteenth centuries. The eco balance has been under serious threat by the industrial pollutants and the carbon emissions from auto mobiles and from many other creatures of comfort which man has created for himself and by extracting the natural environment such as land, coal, minerals, water, trees, etc. as input/resources and in return dumping the waste, polluting the environment, causing atrocious problems such as global warming, floods, drought, famine and many more. Now the corporate citizens have identified their responsibility to do every bit to protect and sustain environment. Need of a realistic environmental management drive all over the world towards various solutions, one of which is green HRM. In the present scenario Green Human Resource Management (GHRM) has become a fashionable business strategy for the organizations who works on ethical philosophy and goodwill is the prime objective for them. This article is throwing the light on the terms and concepts of green HRM, briefly discuss why going green is important and also examining the reason that organizations are adopting a green HRM philosophy along with the challenges of going green.